FICTITIOUS STORY OF INDEPENDENT WOMEN: ANALYSIS OF MAIN CHARACTERS’ ROLES IN NEW DISNEY PRINCESS MOVIES - Dita Palupi (Department of Master of Linguistic, Universitas Airlangga, 2019)
The former Disney Princess movies mostly, if not all, represent women as the ones who are helpless and require men to save them. However, this representation of women is then altered by Disney, who eventually attempts to change the representation of women into the ones who are independent and able to do things by themselves. This study aims to inspect the similarities in three new Disney Princess movies, that is Tangled (2010), Frozen (2013), Moana (2016), particularly in the main characters’ roles and the princesses’ independent acts. The theory of characters of fairy tales (Propp, 1968) is employed in investigating the characters in the movies, then the theory of feminism (Tyson, 2006) is utilized in observing the role of princess characters in the movies. The results demonstrate that there are three main roles in the movies, that is the princess who conducts the quest, the hero who assists the princess in conducting the quest, and the villain who attempts to seize the advantage from the princess. From this result, it can be concluded that although Disney attempts to represent its princesses as the independent women, it still does not let the princesses conduct their quest without any help from men. This is caused by the lack of self-confidence they suffer as women, who mostly think that they are not as good as men in accomplishing a quest.